1993
DOI: 10.1111/j.1532-5415.1993.tb06488.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Disease in the Elderly

Abstract: Thyroid disease in the aged, both hypothyroidism and hyperthyroidism, may be subtle or may be present with no clinical symptoms and signs, and is therefore difficult to diagnose on the basis of clinical evaluation. The help of the laboratory is essential in making the diagnosis of disease of the thyroid. Therapeutic strategies are different in the aged than in the younger adult with thyroid disease. It is essential for geriatricians, and all clinicians who care for the elderly, to have a solid understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 93 publications
1
17
2
1
Order By: Relevance
“…The result was compatible with the findings of other similar studies [11,16]. It suggested that elevated TSH values directly reflect impaired thyroid hormone production.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The result was compatible with the findings of other similar studies [11,16]. It suggested that elevated TSH values directly reflect impaired thyroid hormone production.…”
Section: Discussionsupporting
confidence: 83%
“…Assessment of thyroid status in geriatric patients has been widely discussed in recent years [14][15][16]. The estimates of the prevalence of thyroid diseases in the elderly depend in part on the sampling methods.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid glands affected with autoimmune disorders may show a hypoechoic pattern (15,16) caused by increased cellularity and a variable degree of lymphocytic infiltration (17). These structural changes usually precede the detection of autoantibodies in the serum and other laboratory abnormalities (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Esta dificuldade técnica se deve, provavelmente, à presença de cifose cervical, que desvia a traquéia para trás e para baixo, dificultando a palpação adequada da glândula e a estimativa do tamanho (14). Em nossa amostra, a palpação da tiróide foi inadequada em 33,7% dos idosos, o que torna importante a realização de ultra-som, principalmente nos casos em que o exame clínico é prejudicado.…”
Section: Discussionunclassified